The Evolution of Intein-Based Affinity Methods as Reflected in 30 years of Patent History - Prabhala, Sai Vivek; Gierach, Izabela; Wood, David W. (Frontiers in Molecular Biosciences, 2022)
Self-cleaving affinity tags, based on engineered intein protein domains, have been touted as a universal single step purification platform for tagless non-mAb proteins. These approaches provide all of the power and flexibility of tag-based affinity methods, but deliver a tagless target protein suitable for clinical applications without complex process development. This combination of features might accelerate and de-risk biopharmaceutical development by bridging early discovery to full-scale manufacturing under a single platform. Despite this profound promise, intein-based technologies have yet to reach their full potential. This review examines the evolution of intein-based purification methods in the light of several significant intein patents filed over the last three decades. Illustrated with actual key figures from each of the relevant patents, key advances are described with a focus on applications in basic research and biopharmaceutical production. Suggestions for extending intein-based purification systems to emerging therapies and non-protein applications are presented as concluding remarks.